Benjamin and Spinoza on Time and History: Some Reading Paths - Paolo Quintili (Journal of Spinoza Studies)
Only recently have philosophical historiography and Benjaminian studies turned their attention to the relationship between Benjamin and Spinoza’s philosophy, with its possible links of affinity (and distance), regarding the conception of time and history. Here we would like to follow some reading paths recently proposed by various interpreters, of particular interest around Benjamin’s reflections on For the Critique of Violence (1920) and the Theological-Political Fragment (1921-22). From such an analysis emerges the figure of a different conception of historical temporality in the two philosophers, which circumvents, in different ways, both the unilinear, “Oedipal” and Platonic-Christian conception of time and the cyclical and recursive conception of the Stoic matrix, both of which are at the basis of the central western vision of historicity.